AI-Driven Market Insights: Transforming the Competitiveness of Local MSMEs in Bekasi, Indonesia - Novi Lestari; Abdisamad Abdirahman Omar; M. Yani Syafei; Muhammad Eko Purwanto (International Journal of Community Service (IJCS), 2026)
AI-DRIVEN MARKET INSIGHTS: TRANSFORMING THE COMPETITIVENESS OF LOCAL MSMEs IN BEKASI, INDONESIA. This study examines the role of AI-driven market insights in transforming the competitiveness of local Micro, Small, and Medium Enterprises (MSMEs) in Bekasi Regency, West Java, Indonesia. Using a descriptive qualitative approach, the research is based on literature review and secondary data, complemented by empirical insights from the Institution Collaboration for International Community Service 2026. The findings reveal that structured knowledge transfer has enabled MSMEs to understand and begin internalizing Artificial Intelligence (AI) as a strategic tool for analyzing market trends, consumer behavior, and business opportunities. Furthermore, the study identifies a significant increase in digital awareness and literacy among MSME actors, reflected in their shift from intuition-based to data-driven decision-making practices. This transformation is further supported by the emergence of a collaborative ecosystem involving academic institutions, international experts, and local entrepreneurs, which facilitates knowledge co-creation and innovation diffusion. Through triangulation and theoretical dialogue, the study confirms that AI adoption in MSMEs is influenced by knowledge transfer, digital literacy, and ecosystem support. The results highlight that AI-driven market insights are no longer merely conceptual but are increasingly being implemented in local business practices. Therefore, this study contributes to the literature on digital transformation and MSME development by providing empirical evidence of how AI can enhance competitiveness in emerging economies.